Achieving connectedness and cohesion - Ong, Keng Yong (2022)
Diversity, modernity, and most recently, the COVID-19 pandemic, have complicated social relationships across many societies globally. Mutual trust, stronger bonds, and the harnessing of technology are needed to keep diverse communities together. Strengthening social cohesion requires deliberate effort and conviction from everyone.